THE ANALYSIS OF PRESUPPOSITION IN “MALEFICENT” MOVIE - Devian Try Gustary; Nur Laeli Makiah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
The aim of this study is to identify the type and the meaning of presupposition found in Maleficent movie. The writer used qualitative research method to analyze this movie. The data was taken from the characters utterance in the movie and English script for supporting data. The writer applied the theory of presupposition and context that was developed by Yule (1996) to do the analysis of presupposition from the characters in Maleficent movie. This research tried to classify the utterance based on the six types of presupposition and the implied meaning behind it. The writer discovered that there were six types of presupposition found in Maleficent movie which are 67 existential presupposition, 22 structural presupposition, 8 factive presupposition, 6 lexical presupposition, 3 counterfactual presupposition, 2 non-factive presupposition. Existential become the most used presupposition because the characters in the Maleficent movie often talk about the existence of something, such as person, thing, and place. The writer also discovered that the utterance that consist presupposition have implied meaning that is not stated by the speaker.